(3Yde GdCSWQdGHs - (3CHh GdbGSe GdHZOGOj , CHh GdbGSe Hf eMahX, LeGd GdOjf,J (B310 (3g` s
(3ChdgG (B:s
(3SCdfi HYV GdeTJZdjf Ydi ai Yde GdfLhe Cf CdNU dg cJGHkG ai Yde GdCSWQdGH jOQc Hg eG jMJGL Edjg s
(3BNQgG (B:s
(3hjfXQ ce RGd GdeQi Yf ehVYI aeG cGf age bhS fgGQ Pdc GdchcH aEf CQOfG bhS djdI hVYfG TXjI Ydi Cab GdeZQH hYdefG Ydi GdeQi hCOQfG GdYfcHhJ Ydi GdJhGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B113s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdfHi TjJ (B_ (3GdehUd (B(3/77) s
Keywords: (3Gdadcs